Evaluation of depth of dislocation visibility in SEM electron channeling contrast imaging in Ti-6Al-4V alloy using serial sectioning method. (7th October 2020) - Yamasaki, Shigeto; Deguchi, Misaki; Mitsuhara, Masatoshi; Nakashima, Hideharu; Ota, Yutaro; Kubushiro, Keiji
Abstract: In this study, we conducted a quantitative evaluation of dislocation density by scanning electron microscopy electron channeling contrast imaging for α grains of a Ti-6Al-4V alloy deformed at room temperature. The depth of visibility of dislocations is experimentally measured as 140 to 160 nm by a serial sectioning observation. This result is compared with the theoretical value and applied to evaluate dislocation density. These factors confirm that the theoretically calculated value of the depth of visibility, at 5 to 6 times the extinction distance, is valid for the hexagonal close-packed Ti alloy.